Konseptualisasi Pendidikan Multikultural dalam Mewujudkan Karakter Kebangsaan - Supiyardi; Selamet; Ruswandi, Uus; Tjasmini, Mimin; Adrivat, Zul (PT. Pusmedia Group Indonesia, 2024)
National character is the nature and values of a nation shown by its people in their behavior and character. This research discusses how the concept of multicultural education creates character that is in accordance with nationality. In the implementation of multicultural education in schools. First, implement the contribution approach in the classroom. This level is the most frequently implemented and most widely used in the first phase of the ethnic revival movement. Second, Implementation of Additive Education in the Classroom. At this stage, material, concepts, themes and perspectives are added to the curriculum without changing the structure, objectives and basic characteristics. This additive approach is often complemented by books, modules, or subject areas. Third, the transformation approach in the classroom changes the basic assumptions of the curriculum and fosters students' basic competencies in viewing concepts, issues, themes and problems from several perspectives and ethnic points of view. Fourth, the social action approach includes all the elements of the transformation approach, but adds a component that requires students to take action related to the concepts, issues, or problems studied in the unit. Keywords: Conceptualization; Multicultural Education; National Character